Screening and verification of differentially expressed serum proteins in children with severe adenovirus pneumonia - Gao, Zheng-Xiang; Xu, Hong; Yang, Qu; Xie, Liang; Chen, Li-Na; Liu, Han-Min (Frontiers in Public Health, 2024)
BackgroundHuman adenoviruses are prevalent pathogens that cause severe acute respiratory infections. The clinical presentation of the adenoviral pneumonia is varied; in severe cases, they may cause systemic multi-system damages. Currently, early clinical differential diagnosis is difficult under the existing testing methods, the study identified potential biomarkers by screening and validating differentially expressed proteins (DEPs), and aimed at distinguishing between severe and non-severe adenovirus pneumonia in children aged <14 years.MethodsDEPs were identified using data-independent acquisition (DIA) quantitative proteomics technology, and potential biomarkers were further validated using an enzyme-linked immunosorbent assay (ELISA).ResultsTwenty-seven identical DEPs were found in patients with severe adenovirus pneumonia. Among these, 10 were downregulated, and 17 were upregulated. In the protein–protein interaction network, five proteins were located at the center of the functional network. Among these, E-selectin showed significantly higher serum expression levels in the severe adenoviral pneumonia group than in adenoviral pneumonia and control groups (p < 0.001). ELISA results were consistent with the proteomic analyses. The receiver operating characteristic (ROC) curve for E-selectin revealed a sensitivity of 79.31% and a specificity of 96.55%, with an area under the curve (AUC) of 0.92.ConclusionE-selectin has potential as a novel biomarker for severe adenoviral pneumonia, and offers insights for improved diagnosis and clinical management.